2017
DOI: 10.1002/adsc.201700465
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic Enantioselective Synthesis of Dihydropyrano‐ indole Derivatives Bearing Trifluoromethylated All‐Carbon‐ Substituted Stereocenters

Abstract: Malononitrile and isatin‐derived trifluoromethylacrylates underwent a Michael addition/cyclization reaction, a process that was catalyzed efficiently by a bifunctional squaramide to afford a range of dihydropyranoindole derivatives bearing trifluoromethylated all‐carbon‐substituted stereocenters in high yields (up to 99%) with excellent enantioselectivity (up to 98% ee). This transformation was also examined with ethyl cyanoacetate as a nucleophile using a bifunctional thiourea as catalyst affording moderate y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…[61] Liu, Zhao and co-workers developed squaramide B' catalyzed cascade between isatin based trifluoromethyl acrylate 158 and malononitrile 107 in course of synthesizing dihydropyranoindole derivatives 159 bearing a trifluoromethylated quaternary stereocenter. [62] The reaction proceeds through sequential 1,4-addition, O-cyclization, imine-enamine tautomerism steps to afford the products with appreciable chemical yields and enantiocontrol. Electronic nature and position of the substituents in the aryl moiety of 158 had very little influence on the reaction.…”
Section: Synthesis Of Oxacyclesmentioning
confidence: 99%
“…[61] Liu, Zhao and co-workers developed squaramide B' catalyzed cascade between isatin based trifluoromethyl acrylate 158 and malononitrile 107 in course of synthesizing dihydropyranoindole derivatives 159 bearing a trifluoromethylated quaternary stereocenter. [62] The reaction proceeds through sequential 1,4-addition, O-cyclization, imine-enamine tautomerism steps to afford the products with appreciable chemical yields and enantiocontrol. Electronic nature and position of the substituents in the aryl moiety of 158 had very little influence on the reaction.…”
Section: Synthesis Of Oxacyclesmentioning
confidence: 99%
“…Very recently, we synthesised a series of trifluoromethylated methylene oxindoles and further exploration revealed that these substrates underwent an organocatalytic Friedel-Craft alkylation/lactonisation reaction with naphthols or hydroxyindoles to give dihydrocoumarins in high stereoselectivities. 16,17 In continuation of our interest in the development of new methodologies for the synthesis of trifluoromethylated compounds, 18 we herein report a rapid thio-Michael addition of various thiols to trifluoromethylated 3-methylideneoxindoles under catalyst-free conditions.…”
mentioning
confidence: 99%
“…As in the case of glyoxalates, the trifluoropyruvate adducts 4a , 4e and 4f were obtained as single geometrical isomers ( E ‐isomers) though the reaction times were much longer. [ 20 ]…”
Section: Figurementioning
confidence: 99%